2022
DOI: 10.1021/acs.energyfuels.2c02203
|View full text |Cite
|
Sign up to set email alerts
|

Dissolving Nonionic Surfactants in CO2 to Improve Oil Recovery in Unconventional Reservoirs via Wettability Alteration

Abstract: CO2 injection is a promising method for enhanced oil recovery (EOR) in unconventional shale reservoirs. In this work, we postulate that CO2 EOR may be improved by the dissolution of surfactants into CO2. Although CO2 is a relatively good solvent for oil, we show that CO2 and Eagle Ford oil are immiscible at compositions above 70 wt % CO2, even at pressures as high as 62 MPa. The presence of a CO2–oil interface at reservoir conditions indicates that the addition of a surfactant has the potential to improve oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The solubilities of the surfactants in CO 2 were determined using a visual, isothermal, nonsampling method that is described in our previous publication. 35 The experiment was performed in a windowed, variable-volume view cell. The surfactant and liquid CO 2 were injected into a sampling cylinder above a sliding piston.…”
Section: Surfactant Solubility In Comentioning
confidence: 99%
See 1 more Smart Citation
“…The solubilities of the surfactants in CO 2 were determined using a visual, isothermal, nonsampling method that is described in our previous publication. 35 The experiment was performed in a windowed, variable-volume view cell. The surfactant and liquid CO 2 were injected into a sampling cylinder above a sliding piston.…”
Section: Surfactant Solubility In Comentioning
confidence: 99%
“…The stabilities of CO 2 −brine−surfactant foams were measured in the same windowed, variable-volume view cell as described in section 2.3, and our previous publication. 35 To the view cell were added equal volumes of CO 2 (based on CO 2 density at 46 °C and 20 MPa), brine, and surfactant (0.1 wt % relative to the mass of brine). The cell was sealed, the temperature increased to 46 °C and the pressure was increased to 20 MPa.…”
Section: Surfactant Solubility In Comentioning
confidence: 99%
“…The injection of wettability modifiers caused the oil recovery to increase by 25%. Besides that, projects that used systems of nonionic surfactants dissolved in CO 2 as wettability alteration agents in unconventional reservoirs are known. , Such solutions modify the rock surface from oil-wet to water-wet. The gas chromatography analysis conducted after soaking experiments showed that surfactant promoted extraction of heavier oil components.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In light of these challenges, CO 2 injection shows great potential as a complementary energy source for shale formations. 7,8 CO 2 has a relatively high mobility in shale and can dissolve in shale oil to lower its viscosity. 9−11 Furthermore, CO 2 is preferentially adsorbed in kerogen, displacing light hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Shale oil plays a crucial role in supplementing conventional oil resources . However, the primary production of shale oil is often hampered by a low recovery rate (typically at 3–10%). The water injection method, commonly used to replenish conventional reservoir energy, becomes costly for improving shale oil recovery due to the nanometer pore sizes and low permeabilities (from nano- to microdarcy) of shale formations. , In light of these challenges, CO 2 injection shows great potential as a complementary energy source for shale formations. , CO 2 has a relatively high mobility in shale and can dissolve in shale oil to lower its viscosity. Furthermore, CO 2 is preferentially adsorbed in kerogen, displacing light hydrocarbons . As the oil industry aims to meet the net-zero emission goal, CO 2 injection for shale oil recovery aligns with this purpose. , …”
Section: Introductionmentioning
confidence: 99%